Organization and Education System Management in the Hellenic Republic - Vykhrushch, Vira (Pedagogical Discourse, 2019)
In the process of scientific research, it has been established that the Greek education system remains a highly centralized system, since the main competences for educational policy and management are centralized under the responsibility of the Minister of Education, Research and Religion. The main directions of educational policy of Greece are analyzed. The most important questions about the organization and management of education in various branches and sciences in Greece are highlighted. The contents of vocational training, in particular pedagogical, and adult education in Greece are revealed. The Greek higher education system is purely state-owned and decentralized. It has been found that the purpose / employment of teachers is based solely on rating lists. Account is also taken of academic qualifications, social criteria and the actual preliminary pedagogical service. It is determined that the general requirements for the selection of persons to receive a pedagogical education are the citizenship of the Hellenic Republic; good knowledge of the Greek language; moral purity Accordingly, the specific requirements for the selection of persons to receive a pedagogical education are full secondary education; entrance exams. The prospect of further scientific research in this area may be the study of the organizational and pedagogical basis for the professional training of future teachers at the faculties of education of the universities of the Hellenic Republic.